1979
DOI: 10.1037/0278-7393.5.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of process and structure on encoding.

Abstract: The general problem under investigation in this study is the extent to which an orienting activity exerts control over the encoding process. Two experiments are reported in which associative meaningfulness was varied under conditions of semantic and nonsemantic processing. Contrary to assumptions of exclusive encoding control by the orienting task, both experiments showed effects of meaningfulness following both semantic and nonsemantic processing tasks. The results are consistent with previous reports of nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
4
15
2
Order By: Relevance
“…However, the orienting tasks had no reliable, differential effects on performance. This result has precedents in other studies that have found material effects that were independent of orienting tasks (e. g. , Hunt, Elliot, & Spence, 1979). Such results simply indicate that orienting tasks are not always successful in controlling encoding processes and that, in some cases, tobe-remembered material exerts an independent and substantial influence upon encoding.…”
Section: Discussionsupporting
confidence: 81%
“…However, the orienting tasks had no reliable, differential effects on performance. This result has precedents in other studies that have found material effects that were independent of orienting tasks (e. g. , Hunt, Elliot, & Spence, 1979). Such results simply indicate that orienting tasks are not always successful in controlling encoding processes and that, in some cases, tobe-remembered material exerts an independent and substantial influence upon encoding.…”
Section: Discussionsupporting
confidence: 81%
“…Although the results are precisely what one would expect from a levels of processing approach that asserted that encoding processes are the only important determinant of memory, we noted earlier that there was substantial empirical evidence to suggest that semantic attributes of the study material could still influence recall even under low-level orienting tasks (Hunt et al, 1979;Nelson et al, 1979;Till & Jenkins, 1973). In the current experiments this is clearly not the case.…”
Section: Similarity and Long-term Memory For Order 19supporting
confidence: 70%
“…This prediction, while theoretically sound, is at odds with empirical evidence that indicates that semantic attributes still affect performance after low-level processing (Hunt, Elliot & Spence, 1979;Nelson, Walling & McEvoy, 1979;Till & Jenkins, 1973). …”
Section: Similarity and Long-term Memory For Ordermentioning
confidence: 96%
“…Paivio's explanation is similar to that devised by Hunt et al (1979) for a different set of tasks. Independent of the explanation favored, what is clear for processing studies is that orienting tasks involving ratings are not as effective controllers of processing as might be expected.…”
Section: The Free-recall Clustermentioning
confidence: 84%